Development of a fast immunosorbent assay for site-screening dioxin contamination in Vietnam - Dang, Phuong Nam; Nguyen, Van Hoang; Pham, Kien Cuong; Nguyen, Thi Nhung; To, Lan Anh; Le, Duy Khanh; Nghiem, Xuan Truong; Nguyen, Khanh Hoang Viet (Penerbit Universiti Kebangsaan Malaysia, 2023)
Dioxins are a group of chemical compounds that cause environmental pollution and many harmful effects on human health. High-Resolution Gas Chromatography/High-Resolution Mass Spectrometry (HRGC/HRMS) is the standard method for determining dioxin concentrations in soil samples and provides the most accurate results. However, this method is time-consuming, costly, and requires modern equipment. Currently, competitive ELISA is a reliable method used for dioxin detection analysis, offering fast implementation time and low cost. Vietnam is a global hotspot for dioxin contamination, with a high number of dioxin samples for analysis. Therefore, it is essential to optimize this reliable, fast, and low-cost ELISA method for it to be applicable and replace the expensive and complex HRGC/HRMS method currently in use in Vietnam. This study presented optimized conditions for ELISA method using commercial antibodies to detect dioxin. The optimal dilution for the anti-dioxin antibody and the conjugated antibody is 1:2000 and 1:1000, respectively. The reconstitution buffer consists of 50% DMSO/H2 O, with the addition of 0.05% Triton X-100. The incubation time for anti-dioxin antibody incubated with dioxin is 60 min, while the incubation time for Horseradish Peroxidase (HRP) conjugated polyclonal antibody incubated with 3,3’,5,5’-Tetramethylbenzidine (TMB) substrate is 10 min. The quenching time for the enzyme-substrate reaction is 5 min. The half-maximal inhibitory concentration (IC50) of this method is 8500 pg/well and the limit of detection (LOD) is 2.02 pg/well. Although there is a difference between the analytical results of the two methods, the well-correlated results demonstrate the potential of the ELISA method for detecting and screening dioxin contamination before performing confirmatory analysis with HRGC/HRMS. These results serve as the basis for the development of a rapid dioxin detection kit, providing a new and efficient method for detecting and screening dioxin contamination in Vietnam.